Compilation of reputation loss scales in the oil and gas pipeline industry. Issue 1 (29th January 2023) - Chen, Xuefeng; Chen, Wentao; Zhang, Yifu; Peng, Bin; Niu, Meiling; Xu, Mingwei
Abstract: Oil and gas pipeline accidents not only caused personnel casualties, environmental pollution, and economic losses but also brought great panic to the public. In order to prevent accidents, consequence assessment (CA) has been widely used in the oil and gas pipeline industry. It aims to quantify the potential damage or loss due to unexpected eventualities. However, the current CA methods mainly pay attention to tangible loss, that is, human loss, production loss, asset loss, and environmental loss; the intangible loss such as reputation loss is often neglected. This leads to the deterioration of the quality of CA for the oil and gas industry. To settle existing research limitations, this article proposes to compile the reputation loss scale for the oil and gas pipeline industry to measure the intangible loss of oil and gas pipeline accidents. The compilation methodology mainly involves three stages, namely, the selection of reputation loss indicators, a compilation of reputation loss scale based on the Likert scale, and validation of reputation loss scale. The most important innovation is to quantify reputation loss based on the existing research. Therefore, this study can improve the limitations of current CA methodologies for the oil and gas pipeline Industry.